An informal logic of feedback-based temporal control - Tilsen, Sam (Frontiers in Human Neuroscience, 2022)
A conceptual framework and mathematical model of the control of articulatory timing are presented, in which feedback systems play a fundamental role. The model applies both to relatively small timescales, such as within syllables, and to relatively large timescales, such as multi-phrase utterances. A crucial distinction is drawn between internal/predictive feedback and external/sensory feedback. It is argued that speakers modulate attention to feedback to speed up and slow down speech. A number of theoretical implications of the framework are discussed, including consequences for the understanding of syllable structure and prosodic phrase organization.